Formação inicial do professor de geografia na contemporaneidade: entre possibilidades e desafios - Lima, Jhonatas Isac Pereira Nunes (2025)
The rapid evolution of digital technologies has had a profound impact on society and, consequently, on education, redefining modes of interaction, communication, access to information, and the (re)construction of knowledge. In this context of transformation, initia teacher training plays a strategic role, not only in the development of technical skills for the use of digital resources, but above all in the construction of a critical, ethical, and social understanding of the impacts, challenges, and possibilities that technologies offer in the contemporary educational scenario. In view of this, the research was developed based on the following guiding question: how have geography teachers at the São Cristóvão campus of the Federal University of Sergipe (UFS) dealt with or used digital technologies in the training process? Based on this question, the general objective is to understand the insertion of digital technologies in the initial training of geography teachers at the Federal University of Sergipe, whose specific objectives are: to analyze the contributions of digital technologies in the training of geography teachers; to identify the technological interfaces and how they are used in the geography degree course; and to characterize the likely challenges regarding the insertion of DT in the initial training of teachers at UFS. The research adopted a qualitative approach, characterized as a case study, in which the Department of Geography at the Federal University of Sergipe, São Cristóvão campus, constitutes the locus of the research. Data collection was carried out through semi-structured interviews with course professors. Content Analysis was used to analyze the data, according to Bardin (2016). The results indicate that the inclusion of digital technologies in the initial training of Geography teachers occurs in a sporadic, disjointed manner and depends, above all, on the individual initiatives of the professors. Practices focus on the use of geotechnologies, such as QGIS and Remote Sensing, as well as resources such as Canva, Kahoot, and digital quizzes, especially applied in technical subjects and in the components of Supervised Internship. However, this integration is not systematized in the curriculum, nor is it supported by institutional policies or consolidated pedagogical proposals. Despite the limitations, creative practices and meaningful experiences are emerging, reinforcing the need for curriculum review, investment in technological infrastructure, and the development of training policies that ensure the effective, critical, and structural integration of digital technologies into the teacher training process.